2020
DOI: 10.4038/sljch.v49i1.8898
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of complementary feeding in infants aged 6 to 18 months: An application of Health Belief Model

Abstract: Introduction: Complementary feeding plays a vital role in growth and development of children and prevention of malnutrition. Objective:To determine the predictors of complementary feeding in 6 to 18-month-old infants and young children based on the Health Belief Model (HBM). Method:This cross-sectional study was performed on 270 mothers of children aged 6 to 18 months who were randomly selected from those referred to six health centres in Andimeshk city, Iran. Data were gathered using a 53-item questionnaire b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In addition, they should be confident in their ability to perform healthy behaviors. [ 9 15 18 20 ] Alsulaiman and Rentner emphasized the crucial role of high perceived benefits, low perceived barriers, and high self-efficacy to follow the recommended precautionary measures of MERS prevention. [ 22 ] However, on the contrary of the present study, Tang and Wong reported that the perceived barriers did not significantly predict the wearing of facemask to prevent SARS in Chinese adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, they should be confident in their ability to perform healthy behaviors. [ 9 15 18 20 ] Alsulaiman and Rentner emphasized the crucial role of high perceived benefits, low perceived barriers, and high self-efficacy to follow the recommended precautionary measures of MERS prevention. [ 22 ] However, on the contrary of the present study, Tang and Wong reported that the perceived barriers did not significantly predict the wearing of facemask to prevent SARS in Chinese adults.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to maintain long preventive behaviors time against COVID-19, the individuals should have high self-efficacy. [ 18 19 20 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The knowledge and attitude of people toward COVID-19 will play a significant role in preventing and subsequently reducing the morbidity and mortality of the disease [19]. The findings of similar studies during SARS (2003) and MERS (2014) outbreaks showed that people's knowledge and attitudes played a substantial role in their preventive behaviors [19], [20], [21]. The assessment of people's knowledge, attitude, and practice levels toward COVID-19 can be a very important step to assess the health educational needs and planning the effective interventions to fight the disease [22], [23].To the best of our knowledge, the present study is carried out, for the 1 st time, to assess the knowledge, attitude, practice, and fear of the general Iranian population regarding COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…. ‫ﺗﺌﻮر‬ ‫ی‬ ‫ﻫﺎ‬ ‫ی‬ ‫اﺟﺘﻤﺎﻋﯽ‬ ‫ﺷﻨﺎﺧﺖ‬ ‫ﺗﺌﻮری‬ ‫ﻗﺒﯿﻞ‬ ‫از‬ ‫رﻓﺘﺎری‬ [9,10] ‫ﺗﺌﻮری‬ ، ‫رﻓﺘﺎر‬ ‫ﺑﺮﻧﺎﻣﻪ‬ ‫ر‬ ‫ﯾ‬ ‫ﺰ‬ ‫ی‬ ‫ﺷﺪه‬ [11] ‫ﺗﻐﯿﯿﺮ‬ ‫ﻣﺮاﺣﻞ‬ ‫ﻣﺪل‬ ، [12,13] ‫اﻋﺘﻘﺎد‬ ‫ﻣﺪل‬ ‫و‬ ‫ﺑﻬﺪاﺷﺘﯽ‬ [14,15] ‫رﻓﺘﺎرﻫﺎی‬…”
mentioning
confidence: 99%